Navigation: Home > Science Jokes > Content

# N equals N plus one

Theorem: n=n+1

Proof:(n+1)^2 = n^2 + 2*n + 1

Bring 2n+1 to the left:(n+1)^2 - (2n+1) = n^2

Substract n(2n+1) from both sides and factoring, we have:(n+1)^2 - (n+1)(2n+1) = n^2 - n(2n+1)

Adding 1/4(2n+1)^2 to both sides yields:(n+1)^2 - (n+1)(2n+1) + 1/4(2n+1)^2 = n^2 - n(2n+1) + 1/4(2n+1)^2

This may be written:[ (n+1) - 1/2(2n+1) ]^2 = [ n - 1/2(2n+1) ]^2

Taking the square roots of both sides:(n+1) - 1/2(2n+1) = n - 1/2(2n+1)

Add 1/2(2n+1) to both sides:n+1 = n

[Tag]:N equals N plus one

[Time]:5/9/2010

[Time]:5/9/2010

Search

Related

Others